2015
DOI: 10.5944/ap.12.2.10774
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre propensión, sensibilidad al asco y selección de rama profesional

Abstract: ResumenLos modelos tradicionales han sugerido que el asco es una emoción básica con componentes cognitivos, fisiológicos y conductuales distintivos, que actúa para prevenir la contaminación y la enfermedad. Del mismo modo que ocurre con el miedo, el asco podría desempeñar una función claramente adaptativa. En el presente trabajo queremos examinar si la sensibilidad al asco puede tener relación con la orientación laboral en jóvenes. La muestra estuvo compuesta por estudiantes de un centro de formación profesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(30 reference statements)
1
0
0
Order By: Relevance
“…In this sense, it was found that the moderate anxiety levels provoked with the bread with mold and the rotten meat were higher than the ones induced by the garbage bag and the shoe. These results can be related to the fact that taste is the sense that most relates with disgust, which is the most sensitized emotion in patients with OCD and which can generate anxiety (Pineda et al, 2015;Bhikram et al, 2017;Knowles et al, 2019). These findings agree with previous studies that show that edible contaminated stimuli generate more disgust and anxiety responses than nonedible ones (Vicario et al, 2017).…”
Section: )supporting
confidence: 90%
“…In this sense, it was found that the moderate anxiety levels provoked with the bread with mold and the rotten meat were higher than the ones induced by the garbage bag and the shoe. These results can be related to the fact that taste is the sense that most relates with disgust, which is the most sensitized emotion in patients with OCD and which can generate anxiety (Pineda et al, 2015;Bhikram et al, 2017;Knowles et al, 2019). These findings agree with previous studies that show that edible contaminated stimuli generate more disgust and anxiety responses than nonedible ones (Vicario et al, 2017).…”
Section: )supporting
confidence: 90%